Dynamic SWOT analysis : developer's guide : strategic situation diagnostics and project decision making for performance-inspired managers /: developer's guide : strategic situation diagnostics and project decision making for performance-inspired managers. ([1992]) - Dealtry, T. Richard
No abstract available